Composition and Diversity of CRISPR-Cas13a Systems in the Genus Leptotrichia - Watanabe, Shinya; Cui, Bintao; Kiga, Kotaro; Aiba, Yoshifumi; Tan, Xin-Ee; Sato’o, Yusuke; Kawauchi, Moriyuki; Boonsiri, Tanit; Thitiananpakorn, Kanate; Taki, Yusuke; Li, Fen-Yu; Azam, Aa Haeruman; et al. (Frontiers in Microbiology, 2019)
Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas13a, previously known as CRISPR-C2c2, is the most recently identified RNA-guided RNA-targeting CRISPR-Cas system that has the unique characteristics of both targeted and collateral single-stranded RNA (ssRNA) cleavage activities. This system was first identified in Leptotrichia shahii. Here, the complete whole genome sequences of 11 Leptotrichia strains were determined and compared with 18 publicly available Leptotrichia genomes in regard to the composition, occurrence and diversity of the CRISPR-Cas13a and other CRISPR-Cas systems. Various types of CRISPR-Cas systems were found to be unevenly distributed among the Leptotrichia genomes, including types I-B (10/29, 34.4%), II-C (1/29, 2.6%), III-A (6/29, 15.4%), III-D (6/29, 15.4%), III-like (3/29, 7.7%) and VI-A (11/29, 37.9%), while 8 strains (20.5%) had no CRISPR-Cas system at all. The Cas13a effectors were found to be highly divergent with amino acid sequence similarities ranging from 61% to 90% to that of L. shahii, but their collateral ssRNA cleavage activities leading to impediment of bacterial growth were conserved. CRISPR-Cas spacers represent a sequential achievement of former intruder encounters, and the retained spacers reflect the evolutionary phylogeny or relatedness of strains. Analysis of spacer contents and numbers among Leptotrichia species showed considerable diversity with only 4.4% of spacers (40/889) were shared by two strains. The organisation and distribution of CRISPR-Cas systems (type I-VI) encoded by all registered Leptotrichia species revealed that effector or spacer sequences of the CRISPR-Cas systems were very divergent, and the prevalence of types I, III and VI was almost equal. There was only one strain carrying type II, while none carried type IV or V. These results provide new insights into the characteristics and divergences of CRISPR-Cas systems among Leptotrichia species.